Formação de professores : saberes, desafios e possibilidades no trabalho pedagógico do professor de matemática - Teixeira, Eliana Maria Mallmann (2018)
This study aimed to investigate the pedagogical knowledge used in the teaching practice of a group of mathematics teachers and the way they were constructed. The participants were twelve teachers from municipal, state and private schools in Porto Alegre, Rio Grande do Sul. As data collection instruments were used semi-structured interviews and observations regarding teaching practice. The answers given by the teachers were analyzed qualitatively through the Discursive Textual Analysis method, relating them to the questions observed in the classroom. As theoretical contributions that served as basis for this research were used authors such as Tardif (2014), Nóvoa (1995), García (1999), Imbernón (2010), D'Ambrosio (2014), Pimenta (2012) among others. From the data analysis emerged four categories: the teachers' perceptions about the strategies and teaching resources of Mathematics used in the teaching action; the teachers' perceptions of their initial and continuing education; continuous training actions that teachers participate in the service; the teachers' perceptions about the planning of Mathematics classes. From these categories it was possible to delineate the questions related to the data collected from where the intermediate categories emerged. It is possible to affirm that when teachers use contextualization, different strategies and didactic resources in pedagogical practice in the classroom planning, the students present greater motivation and ease of understanding the mathematical concepts. As for the knowledge built in initial and continuous training, it was verified that teachers use different knowledge in their teaching, emphasizing the pedagogical knowledge, vocational training knowledge, curricular knowledge and emphasize the importance of content knowledge and knowledge experiences. It was found that training in schools still has sequels, and it is necessary for teachers to seek their own continuing education beyond school, in seminars, congresses or in postgraduate courses.